BIN1 inhibited tumor growth, metastasis and stemness by ALDH1/NOTCH pathway in bladder carcinoma - Si-yu Chen; Ya-long Zhang; Xiao-ran Li; Ji-rong Wang; Kun-peng Li; Shun Wan; Jian-wei Yang; Hao Wang; Jin-long Cao; Chen-yang Wang; Xin-peng Fan; Sheng-jun Fu; et al. (Hereditas)
Abstract Background Bladder cancer (BLCA) represents one of the most prevalent urological malignancies worldwide. Bridging integrator 1 (BIN1), a well-characterized tumor suppressor that interacts with and inhibits oncogenic Myc transcription factors, has demonstrated crucial roles in various cancer types. However, its specific functions and underlying molecular mechanisms in BLCA development and progression remain poorly understood. This study aims to elucidate the role of BIN1 in regulating BLCA cell proliferation, metastasis, and cancer stem cell properties. Methods Using urinary proteomics analysis, we identified BIN1 as a significantly dysregulated protein in BLCA. The clinical significance of BIN1 was further validated through comprehensive analyses of public databases. BIN1 expression levels defined distinct molecular and immunological subtypes of BLCA. Through proteomic profiling of BIN1-overexpressing UMUC3 cells and corresponding controls, we identified ALDH1 as a key downstream effector in the BIN1-regulated ALDH1/NOTCH signaling axis. We employed multiple experimental approaches, including Western blot analysis, quantitative RT-PCR, immunofluorescence staining, wound healing assays, transwell migration assays, colony formation assays, tumor sphere formation assays, flow cytometry, CCK8 proliferation assays, and cell transfection experiments. Results We observed significant downregulation of BIN1 in both BLCA tissues and cell lines compared to normal adjacent tissues and SV-HUC-1 cells, respectively. BIN1 overexpression inhibited cancer cell proliferation by promoting apoptosis and suppressed epithelial-mesenchymal transition (EMT), thereby reducing local invasion and distant metastasis. Additionally, BIN1 regulated cancer stem cell properties through modulation of ALDH1 expression, with NOTCH2 acting as a crucial downstream mediator of ALDH1 signaling. Conclusion Our findings demonstrate that BIN1 functions as a tumor suppressor in BLCA and suggest its potential utility as both a diagnostic biomarker and therapeutic target for BLCA treatment.